Patient‐reported adherence and persistence to topical treatments for actinic keratosis: a longitudinal diary study. (19th September 2016) - Erntoft, S.; Norlin, J.M.; Pollard, C.; Diepgen, T.L.
Abstract : Linked Comment: Cardwell and Feldman. Br J Dermatol 2016;175 :872 .